Numerical Analysis of Therapeutic Effects by Varying Slot Numbers and Slot-to-Slot Distance in Microwave Ablation Using Multislot Coaxial Antenna - Kim, Donghyuk; Kim, Hyunjung (International Journal of RF and Microwave Computer-Aided Engineering, 2024)
Microwave ablation (MWA) is based on the energy absorbed by biological tissue through microwave emission, which raises the temperature of the tumor to perform the treatment. MWA has the advantage of causing minimal bleeding and treating deep tumors. In this study, MWA for various slot design situations in a microwave coaxial antenna (MCA) was simulated through numerical analysis. For the slot design, the number of slots and the distance between slots were determined by the analysis parameters. A tumor developed inside the liver tissue was implemented, and the temperature distribution of the tumor and surrounding liver tissue was calculated for all cases selected for numerical analysis. The Helmholtz electromagnetic equation was used to calculate the electromagnetic field inside the tissue, and the modified Pennes bioheat equation was used to calculate the temperature change in the tissue due to the emitted microwave. Treatment effects were quantitatively analyzed for each slot design condition through an apoptotic variable based on the calculated temperature distribution. Lastly, conditions that produce optimal treatment effects were derived depending on the number of slots. The analysis showed that as the distance between the slots increased from 0.5 to 3.5 mm, the optimal treatment effect was obtained when the number of slots was 4, 3, 3, and 2, respectively, and the microwave input power at that time was 3.0, 2.8, 2.6, and 3.0 W, respectively. This is expected to allow for more rigorous and more therapeutically effective MWA.
Keywords: Coaxial antennas; Liver tissue; Microwave ablation; Multi-slots; Optimal treatment; Slot numbers; Slot-to-slot distance; Therapeutic effects; Thermal damage; Treatment effects; apoptosis; microwave ablation; slot number; slot-to-slot distance; thermal damage